Men, Muscles, and Eating Disorders: an Overview of Traditional and Muscularity-Oriented Disordered Eating - Lavender, Jason M.; Brown, Tiffany A.; Murray, Stuart B. (Current psychiatry reports, 2017)
Purpose of Review There is growing recognition that eating disorder (ED) symptoms, particularly those of a muscularity-oriented nature, are more common in men than previously understood. The purpose of the current review is to describe contemporary directions and implications of research on traditional and muscularity-oriented ED symptoms among males. Recent Findings Evidence indicates that ED symptoms occur in a substantial minority of men. Importantly, recent research has focused on muscularity-oriented body image and disordered eating in males, demonstrating the prevalence, correlates, and consequences of maladaptive muscularity-oriented attitudes and behaviors. A growing number of assessments are available to measure these constructs in males, and preliminary treatment considerations have begun to be addressed in the literature. Summary Research on male EDs and body image is increasingly focusing on muscularity-oriented manifestations. Continued empirical work will be critical to improve our understanding of the onset, maintenance, and treatment of muscularity-oriented disordered eating in males.